2019
DOI: 10.1111/jdv.15820
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects between air pollution and meteorological factors on the hospital outpatient visits for atopic dermatitis in Beijing, China: a time‐series analysis

Abstract: Background The prevalence of atopic dermatitis (AD) dramatically increased over these years and environmental factors were considered as potential contributors towards these trends. Objective This study aimed to explore several major environmental exposures, including air pollution, temperature and relative humidity, in order to identify potential modifiable risk factors and their interactive effects on AD. Methods We applied a bivariate response surface model and stratification model based on time‐series Pois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 44 publications
(94 reference statements)
7
40
0
Order By: Relevance
“…In contrast, Li et al (2016) found that estimates of NO 2 associated with outpatient visits of eczema were much higher in the warm season (Li et al 2016). Guo et al (2019) observed that when the temperature was high, NO 2 showed a strong positive association with outpatient visits for atopic dermatitis (Guo et al 2019). For different specific skin diseases, exposure levels and time, along with individual confounders (such as age, gender, smoking, socioeconomic status, and habits), may partially explain the inconsistency.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, Li et al (2016) found that estimates of NO 2 associated with outpatient visits of eczema were much higher in the warm season (Li et al 2016). Guo et al (2019) observed that when the temperature was high, NO 2 showed a strong positive association with outpatient visits for atopic dermatitis (Guo et al 2019). For different specific skin diseases, exposure levels and time, along with individual confounders (such as age, gender, smoking, socioeconomic status, and habits), may partially explain the inconsistency.…”
Section: Discussionmentioning
confidence: 97%
“…However, with an odds ratio of 1.05 and the small quantity of observational, cohort studies, and individual studies, the statistical power of this meta-analysis is limited. Several new studies have been published that were not included in this meta-analysis [54][55][56][57][58][59][60]. More recently, Krämer and co-workers have reviewed this evidence by combining data from 57 environmental epidemiological studies in a systematic review [61].…”
Section: Epidemiologymentioning
confidence: 99%
“…It has been reported that air pollutants might increase the risk of COVID-19 (Coccia 2020, Martelletti and Martelletti, 2020, Zhao et al 2014. To the best of our knowledge, interactive effects of air pollutants and meteorological factors have not previously been identified as affecting COVID-19 cases but they have been identified in the noninfectious diseases (Guo et al 2019, Huang et al 2017, McCormack et al 2016 and cause-specific diseases (Chen et al 2019). We also notice a report about the significant interaction effect between PM 10 and the mean temperature on influenza (Xu et al 2013b).…”
Section: Discussionmentioning
confidence: 68%